Impact of Post-Process Heat Treatments Performed on Ti6Al4V Titanium Alloy Specimens Obtained Using LPBF Technology - Silvia Gaiani; Elisa Ferrari; Marica Gozzi; Maria Teresa Di Giovanni; Magdalena Lassinantti Gualtieri; Elena Colombini; Paolo Veronesi (Technologies, 2023)
Additive manufacturing technology has emerged over the past decade as one of the best solutions for building prototypes and components with complex geometries and reduced thicknesses. Its application has rapidly spread to various industries, such as motorsport, automotive, aerospace, and biomedical. In particular, titanium alloy Ti-6Al-4V, due to its exceptional mechanical properties, low density, and excellent corrosion resistance, turns out to be one of the most popular for the production of parts with additive manufacturing technology across all the market segments listed above. However, when producing components using Laser Powder Bed Fusion (LPBF) technology, it is always necessary to perform appropriate heat treatments whose main purpose is to reduce the residual stresses typically generated during the manufacturing process. Post-process heat treatments on Ti6Al4V components obtained by way of additive technology have been extensively studied in the literature, with the aim of identifying optimal thermal cycles, which may allow for the effective reduction of residual stresses combined with proper microstructural conditions. However, despite the usual target of maximizing relevant mechanical properties, it is mandatory for industrial production to achieve a robust process, i.e., minimizing the sensitivity to noise-induced variation. Therefore, the aim of the present work is to compare several post-process heat treatment strategies by performing different thermal cycles in the temperature range of 750–955 °C and investigating how these affect the average mechanical properties and their variance. The treated samples are then analyzed running a complete mechanical and microstructural characterization, and the latter particularly focused on the determination of the typical microstructure present in the treated samples by using the XRD technique.